A critical review of established tinnitus patient-reported outcomes as measures of Tinnitus Severity and Tinnitus Distress and exemplar analysis of the Tinnitus Handicap Inventory as a formative or reflective measure - Clarke, Nathan A.; Hoare, Derek J.; Trigg, Andrew (Frontiers in Audiology and Otology, 2024)
Tinnitus Severity and Tinnitus Distress are frequently referenced and conflated constructs in research, measured using established tinnitus patient-reported outcome measures (PROs). Confusion regarding these constructs and their relation to fundamental scientific conceptions of tinnitus represents a threat to the validity of PROs as applied in tinnitus research, the conclusions that are reached when applying them, and subsequent progress of theory and clinical interventions for those experiencing tinnitus. Therefore, we critically review relevant literature, providing the Severity of Symptoms (SoS) and Correlates of Complaint (CoC) framework to link tinnitus theory to these constructs. We provide researchers with an overview of latent variable fundamentals (including distinctions between formative and reflective measures, and psychometric and clinimetric measurement traditions). We then provide a synthesis of the relationship between Tinnitus Severity and Tinnitus Distress, the SoS/CoC framework, and latent variable measurement to elucidate their distinctions. Finally, we take the Tinnitus Handicap Inventory (THI) as an exemplar of established tinnitus PROs and use study data (N = 200) to empirically evaluate the appropriateness of the THI as a reflective measure of Tinnitus Distress. Subsequently, conceptual and criterion mediation tests provide evidence that the THI is not a reflective measure of Tinnitus Distress according to the CoC conception and should be considered as a formative measure. Researchers should therefore consider whether established tinnitus PROs, such as the THI, are congruent with the scientific conceptions and subsequent theories that they aim to evaluate.